Reflected radiation from a barley crop - Shaharuddin B. Ahmad, (Universiti Kebangsaan Malaysia, 1980)
Reflected radiation or albedo from a barley crop was measured from April till September 1978, using two Kipp and Zonen solarimeters and two types of Infrared Thermometers. Seasonal mean value of albedo 23.4 percent was obtained with maximum monthly value established during full ground cover i.e., in June. Linear regression equations relating measurements of normalized abledo on ground cover, leaf temperature, leaf water content respectively, were obtained. Although the better positive correlation was calculated for ground cover, the other two crop parameters seemed to have influenced on the normalized albedo in the form of negative correlations.